PENERAPAN MODEL PEMBELAJARAN PDEODE UNTUK MENINGKATKAN MOTIVASI BELAJAR FISIKA SISWA KELAS XI IPA SMA NEGERI 1 RENGAT - ', Irma I; ', Zulhelmi; ', Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aimed to determine students 'motivation to learn physics through the application of learning models PDEODE and know the difference between the students' motivation to learn physics class that implements the learning model Predict, Discuss, Explain, Observe, Discuss, Explain (PDEODE) with a class that implements the conventional learning. This type of research is a Quasi-experimental, with the draft Non-equivalent control group design. The subjects in this study is a class XI IPA 3 with the application of learning models PDEODE and class XI IPA 5 with the application of conventional learning. The data in this study a questionnaire score students' motivation to learn physics after learning model application PDEODE were analyzed descriptively. Further differences between the students' motivation to learn physics class that implements the learning model PDEODE with a class that implements the conventional study were analyzed using N-Gain. Based on the analysis of data obtained by the N-gain average of students in classes that implement learning models PDEODE middle category with an average N-Gain 0.34, while in the class that implements the conventional learning motivation to learn the average student is at the low category with an average N-Gain 0.12. It can be concluded that the application of learning models PDEODE can increase the motivation to learn physics class XI IPA at SMAN 1 Rengat. Key Words: PDEODE learning, motivation learn.